Ostarine and Ligandrol Improve Muscle Tissue in an Ovariectomized Rat Model - Roch, Paul Jonathan; Henkies, Danny; Carstens, Jan Christoph; Krischek, Carsten; Lehmann, Wolfgang; Komrakova, Marina; Sehmisch, Stephan (Frontiers in Endocrinology, 2020)
In postmenopausal women, hormonal decline changes muscle function and structure. The non-steroidal selective androgen receptor modulators (SARMs) Ostarine (OS) and Ligandrol (LG) have been shown to increase muscle mass and physical function while showing a relative low risk profile. Information about their effects on muscle structure and metabolism is lacking. To analyze this, two experiments were performed using ovariectomized rats as a standard model for postmenopausal conditions. In each experiment, 3-month old Sprague-Dawley rats were divided into five groups (n = 12 to 15). One group remained intact (Non-OVX), the other four groups were ovariectomized (OVX) and remained untreated for eight (OS Experiment) or nine (LG Experiment) weeks. Thereafter, rats of three of the four OVX groups were treated with OS or LG (with doses of 0.04, 0.4, or 4 mg/kg body weight/day) for five weeks. Then, uterus, gastrocnemius, and soleus muscles were weighed, fiber size, capillary density, and enzyme activity (lactate dehydrogenase [LDH], citrate synthase [CS], and complex I) were analyzed. In the LG experiment, intramuscular fat content was determined in the quadriceps femoris muscle. All OS treatments resulted in a higher capillary density in the gastrocnemius and longissimus muscles compared with the Non-OVX and the OVX rats, whereas all LG treatments showed a higher capillary density compared with the Non-OVX group. Muscle fiber size and distribution patterns were not changed under either SARM. The CS activity was higher in the longissimus muscle under OS treatment. LG resulted in a higher activity of CS in the gastrocnemius and of LDH in the longissimus muscle. Both SARMs showed an uterotrophic effect, OS at 4 and 0,4 mg dosages, LG at 4 mg dosage. In sum, beneficial effect on muscle vascularization was observed for both SARMs with a stronger impact for OS. LG showed more effect on muscle metabolism. However, a higher muscle weight and intramuscular fat content observed after LG treatment (4 mg) as well as an uterotrophic effect of both SARMs at higher dosages could be considered as an unfavorable side effects and might be a limitation for their application at these dosages.